Nutrition knowledge and dietary intake among Indonesian professional weightlifters: Implications for performance and policy - Hasan, Muhamad Fahmi; Apriantono, Tommy; Ramania, Nia Sri; Solikah, Nur Luthfiatus; Latief, Gifran (Journal Sport Area, 2025)
Background: In weight-class sports like weightlifting, dietary habits and nutrition knowledge are critical to optimizing body composition and performance. Despite the importance of these factors, limited research has explored the nutritional behaviors and knowledge of elite Indonesian weightlifters. This study addresses that gap by evaluating both dimensions in a professional athletic context. Research Objectives: This study aims to examine the levels of nutritional knowledge and dietary intake among Indonesian professional weightlifters, with the goal of providing recommendations to enhance Indonesia's achievements in the sport. Methods: A cross-sectional study was conducted involving 24 national-level Indonesian weightlifters with at least four years of competitive experience. Participants completed a validated nutrition knowledge questionnaire and a 7-day dietary recall. Data were analyzed using SPSS to determine average intake values and knowledge scores. Findings/Results: Findings revealed that none of the athletes met the recommended dietary intake across all major nutrient categories. Protein intake was the closest to adequacy, while energy, carbohydrate, calcium, and fiber intake were below standard recommendations. Additionally, athletes showed low levels of nutritional knowledge in all assessed areas. Conclusion: Both nutritional knowledge and dietary intake among Indonesian professional weightlifters are inadequate and may hinder optimal performance and recovery. This highlights the urgent need for targeted nutrition education and individualized dietary planning. Future interventions should also consider psychosocial and environmental factors such as food access, cultural influences, time constraints, and social support to ensure sustainable improvements in athletes’ eating behaviors.